The Relationship Between Consumption Patterns, Physical Activity and Sleep Patterns and the Incidence of Obesity in the Jambi Regional Police's National Police Training Center (SPN) - Muhammad Dony Oktari; Silvia Mawarti Perdana; Muhammad Rifqi Azhary; Adelina Fitri; Kasyani (MEDALION Journal: Medical Research, Nursing, Health and Midwife Participation, 2026)
Obesity is a growing health problem among police officers and can reduce physical fitness and work performance. This study aims to analyze the relationship between consumption patterns, physical activity, and sleep patterns with the incidence of obesity among members of the Jambi Regional Police National Police (SPN). This quantitative study used an observational analytical design with a cross-sectional approach. The study population consisted of 109 members, with a sample of 86 respondents selected using simple random sampling. Data were collected using the Food Frequency Questionnaire (FFQ), Global Physical Activity Questionnaire (GPAQ), Pittsburgh Sleep Quality Index (PSQI), and anthropometric measurements. Data analysis was performed using univariate and bivariate methods using the Chi-square test. The results showed a prevalence of obesity of 51.2% and a significant relationship between consumption patterns (p=0.02), physical activity (p<0.001), and sleep patterns (p=0.03) with the incidence of obesity. In conclusion, unhealthy consumption patterns, low physical activity, and disturbed sleep patterns are significantly associated with the incidence of obesity among members of the Jambi Regional Police National Police (SPN).